Food safety knowledge and risk perception among pregnant women: A cross-sectional study in Jordan during the COVID-19 pandemic - Almanasrah, Safaa; Osaili, Tareq M.; Al-Nabulsi, Anas A.; Obeidat, Nail A.; Sindiani, Amer M.; Elsalem, Lina; Alkhalidy, Hana; Mohamad, Maysm N.; Saleh, Sheima T.; Al Daour, Rameez; Al Dhaheri, Ayesha S.; Cheikh Ismail, Leila (Frontiers in Sustainable Food Systems, 2022)
Background Pregnant women are at a higher risk of food poisoning compared to the general population. This can be detrimental to both the mother and the fetus. This study aimed to assess the level of knowledge and risk perception of basic food safety and handling among pregnant women in Jordan amid the COVID-19 pandemic. Methods A descriptive cross-sectional quantitative study among pregnant women in Jordan was conducted using an online questionnaire between November 2020 and January 2021. The survey included socio-demographic data, food safety knowledge, and risk perception questions as well as COVID-19 related questions. A total score for food safety awareness out of 50 was derived for each participant based on the sum of scores from all domains. Student t-test and Analysis of Variance (ANOVA) were conducted using SPSS (Version 26) to compare the mean sum of correct responses of every section (knowledge score) by sociodemographic characteristics. Results A total of 325 participants completed the web-based survey. Most of the participants reported receiving food safety-related information during pregnancy (64.9%). The mean total score for the participants was 23.3 ± 4.6 out of 50 (score percentage 46.6%). Participants were mostly aware of foodborne diseases (82.7%) followed by cleaning and sanitation (51.2%), and personal hygiene (49.1%). The least amount of awareness was observed in the cross-contamination (35.0%), food consumption and safety (35.0%), and temperature control (32.8%) domains. Older participants and those with higher education had significantly higher mean scores (p < 0.001). Most participants agreed that the pandemic had a positive impact on enhancing the measures taken to maintain food safety during the pandemic. Conclusions This study identified gaps in food safety-related knowledge. Educational programs for pregnant women need robust reinforcement within the community. Efficient educational approaches related to food safety should be provided by health care providers and local health authorities. While the COVID-19 pandemic persists, pregnant women must be well-educated about the virus and its prevention strategies to avoid being infected and ensure their baby's safety as well as their own.